Hubungan Inflasi, Suku Bunga, dan Surat Utang Negara di Indonesia - Mulawan, Frediek (Jurnal Ilmiah Mahasiswa FEB, 2014)
This paper analyzes how variables response against any shocks of other variable and to determine the most influential variabel in shaping other variables. The analysis of Vector Autoregression (VAR) or Vector Error Correction Model (VECM) used in this study in particular the test Impulse Response Function (IRF) and test of Variance Decomposition (VDC) in answering this research problem. This study uses secondary data time series from the publications of Directorate General of Debt Management, Bank Indonesia, and BPS from January 2010 to December 2013. The results suggested that the inflation are the important variables in the economy of Indonesia. Inflation has very strong influence of other variables in the long run.Keyword: surat utang negara, inflation, BI rate, and VECM